The Influence of Digital Marketing Strategy and the Application of Information Technology on Go Global Decision Making Implications for Competitive Advantage (Survey on MSMEs in Palu City) - Rena Ayu Purniatin; Abdul Kahar; Masruddin Masruddin; I Putu Edi Darmawan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to examine the influence of digital marketing strategies and the application of information technology on competitive advantage, with the decision to go global as an intervening variable in MSMEs in Palu City. The approach used is quantitative with the Path Analysis method, involving 100 MSME actors selected using purposive sampling techniques. Data collection was carried out through the distribution of questionnaires directly to respondents. The results of the analysis show that digital marketing strategies and the application of information technology have a positive and significant influence on the decision to go global and competitive advantage. In addition, the decision to go global has been proven to be able to act as a mediating variable in the relationship between the two variables to competitive advantage. These findings confirm that the implementation of digital strategies and the integrated use of information technology are important factors in increasing the competitiveness of MSMEs in a sustainable manner.